TECHNOLOGIES AND THEIR USE BY PHYSICAL EDUCATION TEACHERS IN RIO DE JANEIRO (Fiep Bulletin - online, 2017)
This article presents the results of a study with teachers of physical education in the city of Rio de Janeiro, exploringfrom an online questionnaire the technological resources adopted by these teachers in their classes in elementary school. One ofthe objectives of this study was to investigate the use of digital media by teachers of physical education, especially video game,which constitutes a valuable pedagogical tool to be used in the educational process. We collected 160 questionnaires and theresults indicated that 61.9% of the teachers used a stereo, 59% used datashow, 49.6% used computers, 40.3% television andDVD, 25.2% smartphones, 23.7% camera Of photography / filming and 13.7% overhead projector. We highlight that 5% used thevideo game, which reveals the presence of new digital technologies also in public schools.
Keywords: Information and Communication Technology; Exergames; Physical Education